2022
DOI: 10.1177/14673584221119374
|View full text |Cite
|
Sign up to set email alerts
|

Fear of COVID-19, hotel employee outcomes and workplace health and safety management practices: Evidence from Sharm El-Sheikh, Egypt

Abstract: This paper investigates the effect of fear of COVID-19 on employee turnover intention and depression, hypothesizing the mediating effect of psychological well-being and the moderating effect of workplace health and safety management practices. Data was gathered from 687 employees of five-star hotels in Sharm El-Sheikh using a structured survey instrument with time-lag approach. A partial least-square-based path modeling (PLS-PM) was applied to analyze the dataset. The findings reveal the partial mediation of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Even though the ancient Egyptians were known for their sense of humor (Khalid et al , 2022) and were referred to as the “sons of jokes” because of their love of jokes and capacity for laughter in challenging circumstances (Mousa, 2020), hotel employees experienced frequent pressures and anxieties because of their workload (Ma et al , 2021; Valeri, 2022a, 2022b). In the hotel context, work pressure increased because of poor performance, high turnover and hectic environments (Selem et al , 2022a). Leaders have a crucial role in managing firms to ensure their survival and growth, mainly when there are financial difficulties or other crises, which are visible in the world’s economic systems (Zheng et al , 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the ancient Egyptians were known for their sense of humor (Khalid et al , 2022) and were referred to as the “sons of jokes” because of their love of jokes and capacity for laughter in challenging circumstances (Mousa, 2020), hotel employees experienced frequent pressures and anxieties because of their workload (Ma et al , 2021; Valeri, 2022a, 2022b). In the hotel context, work pressure increased because of poor performance, high turnover and hectic environments (Selem et al , 2022a). Leaders have a crucial role in managing firms to ensure their survival and growth, mainly when there are financial difficulties or other crises, which are visible in the world’s economic systems (Zheng et al , 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, most complex business environments are confronted with enormous challenges (Shehawy, 2021). As a result of the new coronavirus (COVID-19) outbreaks’ effects on all industries, particularly the hotel industry (Mkheimer et al , 2022), everyone experienced uncomfortable traveling, which had a severe effect on all vital sectors (Selem et al , 2022a; Toanoglou et al , 2022). Therefore, the World Health Organization’s executive director released rules for stopping international travel to combat coronavirus sickness (Yin and Ni, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Tolksdorf et al (2022) conducted a systematic literature review and found similar results that fear of COVID-19 was a significant predictor of employee turnover. In another study among hospitality workers, Selem et al (2022) reported that fear of COVID-19 reduces employees' psychological well-being, resulting in turnover intention. We extend the literature by contending that a high level of fear regarding COVID-19 will likely reduce employee retention.…”
Section: Fear Of Covid-19 and Er Retentionmentioning
confidence: 98%
“…Furthermore, telecommuting is especially valuable during COVID-19 as it reduces physical contact with coworkers, decreasing the spread and fear of COVID-19 (Iversen et al, 2022). As a result, decreased fear of COVID-19 enhances their retention (Selem et al, 2022;Tolksdorf et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…, health and safety practices, training type, and socio-demographic information of informants. With regards to health and safety practices, a number of instruments have been developed to measure it(Bobo, 2017;Senya, 2017;Selem et al, 2022). Nevertheless, this study adapted health and safety practices put forth by health and safety consultant, Neal Etchells; executive housekeeper at the Mövenpick Resort & Spa Mauritius, Jawahir Purmeswur; executive housekeeper at the Swissôtel Zurich in Switzerland, Christopher Rossbach; and executive housekeeper, Elena Philip of Discovery at Marigot Bay, St Lucia.…”
mentioning
confidence: 99%